Transformasi Spasial Peri-Urban di Sekitar Sungai Ciliwung dan Keberlanjutan Kegiatan Wisata Berbasis Sungai - Mega Sesotyaningtyas; Wiwik D. Pratiwi (Universitas Udayana, 2021)
Peri-urban area has been developed into both residential and tourist development. However, such development has caused serious environmental degradation, as in the case of the development of a peri-urban area of the Ciliwung River. To address this condition, the Komunitas Ciliwung Depok has established Saung Pustaka Air (SPA) as an education and conservation based-tourism. This article aims to describe the spatial transformation taking place around the Ciliwung River in 2009-2019 and to analyze the evolution and the blueprint of the SPA as river-based tourism using the Tourist Area Life Cycle (TALC) Model. This study shows that the conversion from open space into built areas is very significant to note. Meanwhile, the TALC model shows that the SPA is in its